2007
DOI: 10.1093/jee/100.4.1370
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Treatment Success and Patterns of Reinfestation of the Formosan Subterranean Termite (Isoptera: Rhinotermitidae)

Abstract: Spread of the Formosan subterranean termite, Coptotermes fornwsanus Shiraki (Isoptera: Rhinotermitidae), is connected with the transport of infested wood, in particular, railroad ties. Therefore, efficient treatment of infestations, especially along railroads, is imperative to prevent further termite damage and spread. Evaluation of treatment success hinges on the ability to assign infestation sites to colonies and compare colony identity before and after treatment. Because colonies of the Formosan subterranea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The breeding system of a colony does not seem to have an impact on a colonyÕs survival during an inundation event. A similar lack of association between breeding structure and survivorship was noted by Husseneder et al (2007) after treatment. If extended family colonies exhibited a higher probability of surviving inundation because of multiple reproducing pairs residing in satellite nests, there would have been a decrease in the percentage of simple family colonies observed at the research sites after ßooding.…”
Section: Discussionsupporting
confidence: 60%
“…The breeding system of a colony does not seem to have an impact on a colonyÕs survival during an inundation event. A similar lack of association between breeding structure and survivorship was noted by Husseneder et al (2007) after treatment. If extended family colonies exhibited a higher probability of surviving inundation because of multiple reproducing pairs residing in satellite nests, there would have been a decrease in the percentage of simple family colonies observed at the research sites after ßooding.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, small percentages of mixed family colonies were also detected for R. flavipes [13], [39] and R. grassei [41]. Proportions of termite colonies with different breeding systems vary across populations and depend on age structure of the colonies, dynamics of colony-colony interactions, food quantity and quality, soil characteristics and disturbance or treatment [4], [14], [20], [21], [42]. There were plenty of 20–30 years old pine trees and camphor trees in the parks and hills of sample collection in Huanggang, Changsha and Chongqing, suggesting that the R. chinensis colonies had enough time and food to grow and develop into extended families headed by neotenics [35].…”
Section: Discussionmentioning
confidence: 99%
“…P values were obtained by permutations of the multilocus genotypes between each pair of samples and standard Bonferroni corrections were used. If samples significantly differed from each other, they were assigned to different colonies [11], [14].…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of dye characterization, colonies of Coptotermes formosanus Shiraki and all Reticulitermes spp. were characterized by genetic structure using microsatellite markers (Vargo 2003a,b;Husseneder et al 2007). Ten termites were genotyped at each of several microsatellite loci.…”
Section: Methodsmentioning
confidence: 99%
“…Smith et al (2002) reported on the elimination of 53 colonies with hexaßumuron and 74 colonies with novißumuron and concluded that the number of days required for colony elimination with novißumuron was about half that with hexaßumuron. Other studies have demonstrated elimination of subterranean termites with novißumu-ron bait (Getty et al 2007, Husseneder et al 2007, Austin et al 2008.…”
mentioning
confidence: 97%